An innovation of cordial liquid into cordial capsule / Nurul Wahidah Hadi … [et al.] - Hadi, Nurul Wahidah; Daim, Nur Darinna; Ariffin, Siti Hawa; Zahid, Nurul Atiqah; Mohamed Esa, Mashitah (Research Innovation Business Unit, 2014)
Cordial capsule is an innovation that makes people’s lifestyle better and easy going. Cordial capsules have a variety of flavour such as orange, strawberry, grape, lychee and syrup. The taste suit ordinary people and easily accepted by normal people. It has a pure taste of fruits which attracts people to try it. This product is suitable for everyone. Cordial capsule is suitable for people because it can save time. Normally people must add sugar into cordial drink to make the taste good. However, with this new innovation, people do not need to waste their time to prepare the sugar. This cordial capsule includes sugar and people can drink every time they want. They just put one tablet of cordial capsule into plain water and ready to drink it. Cordial capsule is flexible and people can bring it to everywhere they want. It is lighter than cordial liquid. so when people want to do outdoor activities like picnic and camping, they just bring only plain water and capsule cordial. Beside that people can bring it to travel by bring small quantities of cordial capsules which are packaged separately in plastic to avoid damage. In conclusion, cordial capsule has many benefits to the community